G-POSS connected double network starch gels for protein release - TUNCABOYLU, DENIZ CEYLAN; Cosgun, Seyma Nur Kirmic; Tuncaboylu, Deniz Ceylan; Alemdar, Mahinur (My University, 2023)
Starch is one of the most frequently preferred natural polymers in hydrogel synthesis. Herein, we combined two strategies of associating brittle and ductile networks in a structure and incorporating inorganic particles into the polymeric gel to design mechanically enhanced nanocomposite double network (DN) starch gels. For the first time in the literature, nanocomposite starch gels (s-NC) were designed by cross-linking starch chains with 8-armed glycidyl-polyhedral oligomeric silsesquioxane (g-POSS) units. Fourier Transform Infrared Spectroscopy and Energy Dispersive X-Ray Spectroscopy analyses have proven that g-POSS is included in the gel structure and is homogeneously distributed throughout the network. More stable d-NC-DMA and d-NC-VP gels were obtained by incorporating N,N-dimethylacrylamide (DMA), or 1-vinyl-2-pyrrolidinone (VP) units, respectively, into g-POSS-linked starch gels, and the reaction kinetics were followed in situ. In SEM images, it was observed that d-NC-DMA had smaller pores and thicker pore walls compared to s-NC and d-NC-VP starch gels, and its mechanical strength was shown to be much superior by rheological tests, compression, and tensile analyses. In addition to increasing the mechanical strength of the gels, the potential of starch in protein release applications using amylase sensitivity has been demonstrated in vitro experiments using the model protein BSA.
Keywords: Double network; Glycidyl-POSS; Hydrogel; Nanocomposite; Protein release; Starch